Risk and risk premium on international tourism receipts of Asia and the pacific region - Chaiwat Nimanussornkul (2018)
© 2017 Serials Publications Pvt. Ltd. Tourism industry is continuous expansion and becomes the one of major industry in recent decades. The number of international tourist arrivals and international tourism receipts in 2016 are 1,235 million and 1,220 billion US dollars, respectively. Asia and The Pacific region is the highest growth in term of international tourist arrivals. However, the international tourism receipts is volatile. Therefore, the arbitrage pricing theory (APT) is applied to find the risk and risk premium on international tourism receipts of the countries in Asia and The Pacific region. The results show that the change in foreign exchange rate has highly impact on Hong Kong international tourism receipts whereas inflation ratio has more effect to the international tourism receipts for Malaysia, Singapore, the Philippines, and Japan. World GDP growth and world international receipts growth have to concern next and the change in crude oil price, that has lowest impact on international tourism receipts, is the last. Furthermore, the high risk on international tourism receipts is the cause of low expected international tourism receipts.